SIKAP DAN PENGAMBILAN KEPUTUSANPEMBELIAN SAYURAN ORGANIK OLEH KONSUMEN DI KOTA BANDAR LAMPUNG - Ni Made Anggiasari; Yaktiworo Indriani; Teguh Endaryanto (Lampung University, 2016)
This study aims to determine the characteristics of consumers, their attitudes, the stages of the purchasing decision, and the factors that influence the purchase of organic vegetables at Chandra Supermarket in Bandar Lampung City. The research was conducted purposively in Chandra Supermarket of Bandar Lampung city. The number of consumer respondents was 60 people recruited accidentally. Research data were analyzed by using descriptive qualitative and quantitative Fishbein-Multiattribute Model, and Seemingly Unrelated Regression (SUR) analysis. The results showed that the characteristics of consumers of organic vegetables at Chandra Supermarket were dominated by women 25-50 years old. Most consumers were housewives, Senior High School graduates, monthly family income of Rp5.000.000,00 or less,and organic vegetable purchase of 1-4 times a month. The consumer attitude (Ao) was to provide the highest value to the cleanliness. Stages of purchasingdecisions on organic vegetables were the need recognition, information searching,evaluation of alternatives, and post-purchase behavior.Factor that influenced positively on the purchase of organic vegetables was freshness, while factors that influenced negativelywere the ratio of price andincome, the cleanliness, and wholeness of vegetables.Keywords: attitude, cleanliness, organic vegetables, purchasing decisionsThis study aims to determine the characteristics of consumers, their attitudes, the stages of the purchasing decision, and the factors that influence the purchase of organic vegetables at Chandra Supermarket in Bandar Lampung City. The research was conducted purposively in Chandra Supermarket of Bandar Lampung city. The number of consumer respondents was 60 people recruited accidentally. Research data were analyzed by using descriptive qualitative and quantitative Fishbein-Multiattribute Model, and Seemingly Unrelated Regression (SUR) analysis. The results showed that the characteristics of consumers of organic vegetables at Chandra Supermarket were dominated by women 25-50 years old. Most consumers were housewives, Senior High School graduates, monthly family income of Rp5.000.000,00 or less,and organic vegetable purchase of 1-4 times a month. The consumer attitude (Ao) was to provide the highest value to the cleanliness. Stages of purchasingdecisions on organic vegetables were the need recognition, information searching,evaluation of alternatives, and post-purchase behavior.Factor that influenced positively on the purchase of organic vegetables was freshness, while factors that influenced negativelywere the ratio of price andincome, the cleanliness, and wholeness of vegetables. Keywords: attitude, cleanliness, organic vegetables, purchasing decisions